Data Cleansing, Standardization and Data Migration Framework for Proprietary to Open-Source ILMS in India - Mishra, Vinod Kumar; Rath, Durga Sankar (Journal of Information and Knowledge, 2023)
The present study discusses data migration and various issues involved in data cleansing and standardization. Libraries are moving to the popular open-source ILMS Koha. The paper describes the design of a data migration framework from proprietary Integrated Library Management Software (ILMS) to Koha. The issues related to data quality in source ILMS and processes involve understanding and correcting raw data. The paper highlights the methods, tips and tricks, configurations, and data migration in open ILMS Koha. Studies proved Open Source Solutions (OSS) such as Koha for library automation is the better choice as it supports customization at a minimal cost. The paper examines the errors, mistakes and lack of uniformity of data in source databases and methods for quality enhancement of raw data. The current article is of practical significance for those who wish to migrate from existing ILMS to open-source solutions like Koha. The paper covers the migration of bibliographic data, member data and transaction data.